The Analysis Assertive Speech Acts in the Book of Genesis in Indonesian Translation of the Bible - Renata Margareth Libriananda Tobing; Nani Darmayanti; Fahmy Lukman (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The Bible is one of the religious discourses that contains forms of speech acts. One type of speech act which dominates in the Bible is assertive speech act. It is supported by the statements contained in the Bible are dogmatic and filled with a proportion of validity that is believed to be true. One of the scriptures in the Bible is The Book of Genesis. Genesis is the first chapter of the Bible and begins with the story of the creation of the heavens, the earth, and everything in it. Genesis is very important in the history of biblical periodization. Genesis contains a variety of types and forms of assertive speech acts. This research is a qualitative-descriptive study. The data were collected using the read and write technique, then classified and analyzed using the pragmatic equivalent method. Then, the data are presented with descriptive procedure. This research reviewed 20 data of assertive speech acts in the Genesis with details: assertive speech acts-acknowledging amounted to 2 data, assertive speech acts-demanding amounted to 5 data, assertive speech acts-declaring amounted to 6 data, assertive speech acts-giving testimony amounted to 3 data, assertive speech acts announcing amounted to 2 data, and assertive speech acts-reporting amounted to 2 data. Based on the form, assertive speech acts in the book of Genesis are detailed into 15 forms of direct speech acts and 5 forms of indirect speech acts.